2015
DOI: 10.18632/oncotarget.4340
|View full text |Cite
|
Sign up to set email alerts
|

Direct regulation of E-cadherin by targeted histone methylation of TALE-SET fusion protein in cancer cells

Abstract: TALE-nuclease chimeras (TALENs) can bind to and cleave specific genomic loci and, are used to engineer gene knockouts and additions. Recently, instead of using the FokI domain, epigenetically active domains, such as TET1 and LSD1, have been combined with TAL effector domains to regulate targeted gene expression via DNA and histone demethylation. However, studies of histone methylation in the TALE system have not been performed. Therefore, in this study, we established a novel targeted regulation system with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 28 publications
1
12
0
Order By: Relevance
“…Our research demonstrated that the promoter methylation levels of MMP-2 , MMP-7 and MMP-9 in PFTC tissues were considerably lower than those in normal tissues. Two explanations are proposed: one is the decreasing levels of methylation-related DNA methyltransferase of MMP-2 , MMP-7 and MMP-9 in PFTC may lead to failure of methyl to migrate from S-adenosyl- L -methionine to 5′ end of cytosine to facilitate methylation [15,16]; the other possibility is, despite the decreasing methylation levels of the 3 genes, CpG sites located on the transcription factor binding sites have relatively high methylation frequencies. Hu et al [17] showed similar results on Ishikawa and HEC-1A cells.…”
Section: Discussionmentioning
confidence: 99%
“…Our research demonstrated that the promoter methylation levels of MMP-2 , MMP-7 and MMP-9 in PFTC tissues were considerably lower than those in normal tissues. Two explanations are proposed: one is the decreasing levels of methylation-related DNA methyltransferase of MMP-2 , MMP-7 and MMP-9 in PFTC may lead to failure of methyl to migrate from S-adenosyl- L -methionine to 5′ end of cytosine to facilitate methylation [15,16]; the other possibility is, despite the decreasing methylation levels of the 3 genes, CpG sites located on the transcription factor binding sites have relatively high methylation frequencies. Hu et al [17] showed similar results on Ishikawa and HEC-1A cells.…”
Section: Discussionmentioning
confidence: 99%
“…Since there are a wide variety of histone modifications mediated by numerous effectors, programmable enzymes targeting histone tags are also variable compared to those for the DNA modification; e.g., histone demethylase (LSD1 [34,42]), histone methyltransferases (PRDM9 [40], G9a [30,33,50,65] and SUV39H1 [30,33]), and histone acetyltransferase (p300) [66].…”
Section: Targeted Histone Modificationsmentioning
confidence: 99%
“…Especially, G9a, also known as EHMT2, is a lysine 9 of histone H3 methyltransferase, which has been proven to be utilized in cancer modeling [65] and suppression [33,50] as a programmable enzyme. Kim and colleagues demonstrated the cancer modeling with the catalytic SET domain of G9a [65], by showing that cancer malignancy was enhanced in HeLa and HCT116 colon cancer cells.…”
Section: Targeted Histone Modificationsmentioning
confidence: 99%
See 1 more Smart Citation
“…It took a while before this study was followed by ZF-targeting the HER2/neu gene in cancer [66] and even in vivo by targeting the murine  Fosb  gene [67•]. Similarly, authors have fused a TALE, targeting the E - Cadherin gene, and dCas9, in combination with sgRNAs to target VEGF - A , to the SET domain of the histone methyltransferase G9a and demonstrated that this approach is effective in repressing genes, as seen with ZFPs [68, 69]. In the meantime, Zinc Fingers were also exploited in the first DNA methylation targeting studies by fusion to the catalytic domains of DNA methyltransferases Dnmt3a or including a fusion between Dnmt3a and Dnmt3L, which catalyze the de novo methylation of DNA.…”
Section: Epigenetic Repressionmentioning
confidence: 99%